2020
DOI: 10.1371/journal.pone.0228501
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction in intrahepatic cholangiocarcinoma: Direct comparison of the MEGNA score and the 8th edition of the UICC/AJCC Cancer staging system

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 26 publications
0
14
1
Order By: Relevance
“…In the same study, the Wang nomogram reached superior values in estimating prognosis (C-Index 0.72). In two recent evaluations, the MEGNA score was found to be a useful stratification tool but failed in individual risk prediction [ 13 , 29 ]. Thus, none of the scores were implemented in the daily clinical routine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, the Wang nomogram reached superior values in estimating prognosis (C-Index 0.72). In two recent evaluations, the MEGNA score was found to be a useful stratification tool but failed in individual risk prediction [ 13 , 29 ]. Thus, none of the scores were implemented in the daily clinical routine.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them were designed primarily for patients undergoing curative resection and use histopathological factors, such as microvascular invasion or tumor grading, which are only available postoperatively [ 9 , 10 , 11 ]. Even though all attempts have initially shown promising results, they have failed external validation and have not entered clinical use [ 12 , 13 ]. The only available score for all patients regardless of subsequent treatment is the Fudan score [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strengths of this scoring system include external validation and superiority in predicting prognosis and survival to existing models. A comparison of the prognostic separation index between MEGNA and staging systems of the American Joint Committee on Cancer (AJCC) has demonstrated the superiority of MEGNA in patient survival following hepatectomy [ 88 ].…”
Section: Scoring Systemsmentioning
confidence: 99%
“…Current literature highlights substantial heterogeneity in histopathological and genomic characteristics of ICC based on geography [ 87 ]. This heterogeneity is demonstrated in a study by Hahn et al [ 88 ] who evaluated the use of the MEGNA score with a direct comparison of its prognostic value with the AJCC staging system, the most widely used one currently. This study found that the C-index was 0.58 for MEGNA and 0.61 for AJCC, thus demonstrating that the ability of the MEGNA score to predict individual patient prognosis was below the 0.7 threshold of acceptable.…”
Section: Scoring Systemsmentioning
confidence: 99%
“…While proposed as a tool to predict survival following curativeintent liver resection, studies that have externally validated the MEGNA scoring system have been limited due to the small sample size and inclusion of patients from only Western centers. 15,16 Therefore, we sought to assess OS and recurrence-free survival (RFS) utilizing MEGNA in a large cohort of patients undergoing curative-intent resection for ICC using an international multiinstitutional database, comprising of both Eastern and Western countries. In addition, we compared the prognostic ability of MEGNA to other commonly used prognostic systems including the tumor burden score (TBS) and AJCC eighth edition staging system.…”
mentioning
confidence: 99%